CAN THE LIBERAL CONCEPT OF PERSONAL BANKRUPTCY BE A GUIDE TO THE LEGAL REGULATION OF THE SAME IN THE REPUBLIC OF SERBIA AND THE REPUBLIC OF SRPSKA? - Miljković, Strahinja D.; Даниловић, Дамјан (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Unemployment, weak consumer power, inability to regularly service credit obligations (problem loans), inability to settle other financial obligations, may be factors that lead a natural person – consumer to insolvency. An institute that provides the opportunity for a natural person - a consumer to be freed from debts without falling into insolvency at the cost of having his property subject to enforcement is an institute of personal bankruptcy. One of the modalities of personal bankruptcy that should be taken into consideration during future regulation is the liberal model of personal bankruptcy. The liberal model of personal bankruptcy is characterized by an open approach, which in the end leads to complete release - discharge from debt. Debt relief is an essential feature of this model, which is based on the idea of ​​providing a chance for a new financial start (fresh start), which puts the interest of the debtor-consumer in the foreground, and the risk is transferred to the creditor. The legal systems of the Republic of Serbia and the Republic of Srpska do not recognize the institute of personal bankruptcy. The legal norming of the institution of personal bankruptcy is a challenge for the legislation of the Republic of Serbia and the Republic of Srpska, especially because it is not known to court and legal practice, while it is insufficiently considered at the theoretical legal level. For the stated reasons, the authors will point out the advantages and disadvantages of the liberal model, that is, why this model should be taken into consideration during the potential legal regulation of the institute of personal bankruptcy. In this way, the authors try to open the door to a legal discussion about the necessity regarding the legal regulation of the institute of personal bankruptcy in the Republic of Serbia and the Republic of Srpska.